1997
DOI: 10.1093/hmg/6.3.497
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutation clustering in the survival motor neuron gene: a role for a conserved tyrosine and glycine rich region of the protein in RNA metabolism?

Abstract: The Survival Motor Neuron (SMN) gene shows deletions in the majority of patients with Spinal Muscular Atrophy (SMA), a disease of motor neuron degeneration. To date only two missense mutations have been reported in SMN in patients with SMA. The fact that no SMN-homologues have been forthcoming from data-base searching has resulted in a lack of hypotheses concerning the structural and functional consequences of these mutations. Recently SMN has been shown to interact with heterogeneous nuclear ribonucleoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(89 citation statements)
references
References 22 publications
2
85
0
2
Order By: Relevance
“…The over-expression of SMN Functional analysis of mutations in the SMN protein P Mohaghegh et al t proteins also leads to formation of cytoplasmic aggregates. However, deletion of exon 7 abolishes GEM formation consistent with the importance of the YG box 8 and residues in this region for SMN oligomerisation. 9 Furthermore on the same time course, the relative intensity of signal from exon 7 deleted overexpressed SMN protein in the cytoplasm (Figure 2g), to other over-expressed SMN proteins here (Figure 2a, b, c, l) appears weaker.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…The over-expression of SMN Functional analysis of mutations in the SMN protein P Mohaghegh et al t proteins also leads to formation of cytoplasmic aggregates. However, deletion of exon 7 abolishes GEM formation consistent with the importance of the YG box 8 and residues in this region for SMN oligomerisation. 9 Furthermore on the same time course, the relative intensity of signal from exon 7 deleted overexpressed SMN protein in the cytoplasm (Figure 2g), to other over-expressed SMN proteins here (Figure 2a, b, c, l) appears weaker.…”
Section: Resultsmentioning
confidence: 53%
“…For example, it contains a YG box motif which when mutated causes SMA. 8 This YG box is well conserved in S. pombe, C. elegans and mammalian SMN orthologues, and has been shown to be important for the oligomerisation of SMN. 9 Studies by Dreyfuss and colleagues [10][11][12][13] have demonstrated directly that SMN plays a role in RNA processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The centromeric copy of the gene (SMN2) produces mostly an alternatively spliced form of SMN deleted of amino acids encoded by exon 7 (SMN⌬Ex7), and SMN2 can only partially compensate for mutations or deletions in SMN1 (7,15,16). Indeed, some patients, instead of complete deletion of SMN1, have shorter deletions of at least exon 7 or single point mutations within the conserved YG domain (17,18).As measured by coimmunoprecipitation from cytoplasmic extracts, SMN exists in a complex with Sm proteins (19), Gemin2 (formerly SIP1) (19), Gemin4 (20), and the DEAD box RNA helicase Gemin3 (21). The amino terminus of SMN tightly associates with Gemin2, whereas the carboxyl-terminal conserved YG domain is necessary for self-association and interaction with the core snRNP Sm proteins (19,22).…”
mentioning
confidence: 99%
“…The centromeric copy of the gene (SMN2) produces mostly an alternatively spliced form of SMN deleted of amino acids encoded by exon 7 (SMN⌬Ex7), and SMN2 can only partially compensate for mutations or deletions in SMN1 (7,15,16). Indeed, some patients, instead of complete deletion of SMN1, have shorter deletions of at least exon 7 or single point mutations within the conserved YG domain (17,18).…”
mentioning
confidence: 99%